2017
DOI: 10.1021/acs.iecr.7b02494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Surfactants on Alkali Lignin Electrospinning Ability and Spun Fibers

Abstract: Anionic, cationic, and non-ionic surfactants with varying concentrations (0.2-1.2 %)were introduced to neutralize beads on lignin nanofibers by decreasing the surface tension of spinning dopes. The surfactants used in this work were sodium dodecyl sulfate (SDS), N,N,Ntrimethyl-1-dodecanaminium bromide (DTAB), and Triton™ X-100 (TX-100). The effects of viscosity, rheological properties, surface tension, and conductivity of the solutions on the morphology and physicochemical performances of fibers were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 51 publications
1
50
0
1
Order By: Relevance
“…The authors reported that the fiber diameter was 470 nm, which is smaller than those observed in the present study. This discrepancy is due to higher molecular weight of the polymer used in our study than that applied by Gopal et al (2007), that makes the solution more viscose (Fang et al, 2017). respectively.…”
Section: Sem Analysismentioning
confidence: 76%
See 1 more Smart Citation
“…The authors reported that the fiber diameter was 470 nm, which is smaller than those observed in the present study. This discrepancy is due to higher molecular weight of the polymer used in our study than that applied by Gopal et al (2007), that makes the solution more viscose (Fang et al, 2017). respectively.…”
Section: Sem Analysismentioning
confidence: 76%
“…Likewise, Ray et al (2017) indicated that the incorporation of TR-100 into poly vinyl alcohol nanofibrous layer resulted in improving uniformity and homogeneity in fiber diameter (Ray et al, 2017). Fang, Yang, Yuan, Charlton, and Sun (2017) also observed that the addition of TR-100 to lignin-based fibers led to the formation of smooth and bead-free fibers with small diameters. In a study conducted by Gopal, et al (2007), the electrospinning technique was used to fabricate nano-fibers from PSF/DMF solution.…”
Section: Sem Analysismentioning
confidence: 95%
“…This factor depends on the polymer and solvent properties, being controlled by changing their mass ratio (Rogina, 2014; Xue et al., 2019). Uniform fibers can be produced when the surface tension of the solution is reduced at a fixed concentration (Fang, Yang, Yuan, Charlton, & Sun, 2017; Moreira, de Morais, de Morais, da Silva Vaz, & Costa, 2018).…”
Section: Properties Of Electrospun Nanofibersmentioning
confidence: 99%
“…Electrospinning is a simple and multifunctional technique for producing continuous nanofibers [1,2]. It has received lots of attention due to the extensive sources of raw materials, such as synthetic and natural polymers, polymer alloys, polymers loaded with chromophores, nanoparticles, active agents, metals and ceramics, and so on [3][4][5].…”
Section: Introductionmentioning
confidence: 99%